Partitioning of dissolved iron and iron isotopes into soluble and colloidal phases along the GA03 GEOTRACES North Atlantic Transect. (June 2015) - Fitzsimmons, Jessica N.; Carrasco, Gonzalo G.; Wu, Jingfeng; Roshan, Saeed; Hatta, Mariko; Measures, Christopher I.; Conway, Tim M.; John, Seth G.; Boyle, Edward A.
Abstract: The size partitioning of dissolved Fe (dFe<0.2 µm) into soluble (sFe<0.02 µm) and colloidal (0.02 µm<cFe<0.2 µm) species was investigated at 18 stations along the GEOTRACES GA03 North Atlantic Transect. Upper ocean dFe size partitioning was highly variable with depth: 79±6% of aerosol-derived surface dFe was maintained in the colloidal size fraction, while cFe disappeared completely at the deep chlorophyll maximum, presumably a result of preferential cFe biological uptake and/or scavenging. In the intermediate and deep ocean, however, dFe was evenly partitioned ~50:50% into sFe and cFe phases, which we hypothesize results from a "steady state" of dFe exchange reactions during and following remineralization including ligand exchange, sorption/desorption, and aggregation/disaggregation. There were only two exceptions to this constant partitioning in the intermediate/deep ocean. First, cFe dominated (82–96%) at and downstream of the Mid-Atlantic Ridge hydrothermal system. Also, along Line W between Woods Hole and Bermuda the dFe partitioning favored ~60–80% cFe, with the excess cFe likely resulting from inorganic cFe inputs from the margin. Thus, in the North Atlantic Ocean we propose a new model of dFe size partitioning where a "steady state" of dFe exchange reactions during and following remineralization re-partitions intermediate and deep ocean dFe into constantly fractionated sFe and cFe pools, while in the upper ocean, downstream of the Mid-Atlantic Ridge, and along Line W, sFe and cFe appear to cycle more independently, since either not enough time has passed to reach a new dFe exchange steady state or one of the dFe phases is non-labile to dFe exchange. This surface-subsurface decoupling model of North Atlantic dFe size partitioning is supported by Fe isotope ratio analyses of the sFe and dFe size fractions, which recorded isotopically heavy sFe (δ 56 Fe of +1.3‰ to +1.5‰) relative to dFe (δ 56 Fe~+0.5‰) in the surface ocean where sFe and cFe cycle independently, and identical sFe and dFe isotope ratios below 250 m where sFe and cFe are constantly partitioned and exchanged.